Peningkatan Literasi Sejarah Indonesia Melalui Eduwisata ke Museum Pancasila Sakti - Septiono, Wakhid Lukas (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2025)
The specter of history lessons as very boring lessons is no longer a secret. Although this subject has a vital role in forming a generation of a cultured, knowledgeable, and highly competitive nation, the proof is that almost everyone gets the same boredom when studying it. Especially if this lesson is delivered with a conventional approach that tends to place the teacher as the center of learning with a one-way communication. Educational tours to museums can actually be the answer to optimizing history learning, where students become more active because they interact directly with their surroundings and the experiences of their personnel. Educational tours to the Pancasila Sakti Museum with a community education method approach are an effort to improve the understanding of national history. It can be concluded that educational tours to museums are able to provide enrichment and exploration of a more holistic understanding of national history. In addition, physical visualization and direct contact with all historical evidence in the museum are also able to create a sense of satisfaction and stability of historical experience that is more interesting, unique, and memorable. On the other hand, embedding additional materials such as Profession and Aspiration Class and Cultural Class is able to enrich the essence of educational tourism so that the orphanage children not only gain an understanding of the nation's history but also gain a strengthening of belief in the importance of aspiring, continuous learning, and building quality personality through ethical Indonesian language culture.